2013
DOI: 10.1113/jphysiol.2012.248831
|View full text |Cite
|
Sign up to set email alerts
|

Dipeptidyl‐peptidase‐like‐proteins confer high sensitivity to the scorpion toxin AmmTX3 to Kv4‐mediated A‐type K+ channels

Abstract: Key points• AmmTX3, a member of the α-KTX15 family of scorpion toxins, efficiently and specifically blocks the subthreshold-operating A-type K + current in cerebellar granule neurons from wild-type mice but not in neurons from mice lacking the Kv4 channel-associated protein DPP6.• In heterologous cells high-affinity blockade of Kv4.2 and Kv4.3 channels by AmmTX3 requires the presence of the associated proteins DPP6 and DPP10.• These results validate AmmTX3 as a specific blocker of Kv4 channels in CNS neurons a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
47
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 39 publications
2
47
0
Order By: Relevance
“…Rudy and colleagues showed that this agent is highly selective for channels containing K v 4 ␣-subunits in association with DPP6 or DPP10 auxiliary subunits (Maffie et al 2013). We found that unlike 4-AP and BaCl 2 AmmTx3 had no effects on RMP [etv1 (10 cells AmmTx3 application resulted in significant AP broadening (HW and width at threshold) and significant reduction of dV/dt for repolarization in all pyramidal cell subtypes tested, with no changes in voltage threshold (Fig.…”
Section: Resultsmentioning
confidence: 77%
See 3 more Smart Citations
“…Rudy and colleagues showed that this agent is highly selective for channels containing K v 4 ␣-subunits in association with DPP6 or DPP10 auxiliary subunits (Maffie et al 2013). We found that unlike 4-AP and BaCl 2 AmmTx3 had no effects on RMP [etv1 (10 cells AmmTx3 application resulted in significant AP broadening (HW and width at threshold) and significant reduction of dV/dt for repolarization in all pyramidal cell subtypes tested, with no changes in voltage threshold (Fig.…”
Section: Resultsmentioning
confidence: 77%
“…We found that the recently characterized peptide blocker AmmTx3 (200 nM; Maffie et al 2013) was selective for the peak transient A-type current over the steady-state current (and did not affect input resistance or RMP) in neocortical pyramidal cells. These voltage-clamp data with AmmTx3 also indicate that dipeptidyl peptidase-like-proteins (DPP6 or DPP10) Data are means Ϯ SE for 11 (layer 2/3), 10 (etv1), and 10 (glt) cells.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…One interesting case in point is the 744bp long ncRNA, LOC389023 , positioned in chromosome 2q14.1, within the gene body of DPP10 . The DPP10 gene encodes a dipeptidyl peptidase-related protein regulating voltage-dependent potassium channels that control neuronal excitability, membrane repolarization and repetitive firing, back propagation of action potential into dendrites, and dendritic integration and plasticity (Jerng et al, 2005, Zagha et al, 2005, Li et al, 2006, Maffie and Rudy, 2008, Maffie et al, 2013). Interestingly, rare structural variants of DPP10 confer strong genetic susceptibility to autism (Girirajan et al, 2013) and asthma (Torgerson et al, 2012), while some of the gene’s more common variants contribute to a significant risk for bipolar disorder, schizophrenia and asthma (Allen et al, 2003, Marshall et al, 2008, Djurovic et al, 2010, Michel et al, 2010).…”
Section: Human-specific Non-coding Rna Loc389023mentioning
confidence: 99%